Sirt2 epigenetically down-regulates PDGFRα expression and promotes CG4 cell differentiation. Issue 10 (19th May 2019) - Fang, Na; Cheng, Junjun; Zhang, Chu; Chen, Keyuan; Zhang, Chenyu; Hu, Zichao; Bi, Ran; Furber, Kendra L.; Thangaraj, Merlin; Nazarali, Adil J.; Ji, Shaoping
ABSTRACT: We have previously found that Sirt2 enhanced the outgrowth of cellular processes and MBP expression in CG4 cells, where Sirt2 expression is suppressed by transcription factor Nkx2.2. However, the detailed mechanism of Sirt2 facilitating oligodendroglial cell differentiation remained unclear. In the present study, we observed that Sirt2 partially translocated into the nuclei when CG4 cells were induced to differentiate. Sirt2 was detected at the CpG island of PDGFRα promoter via ChIP assay during the cells differentiation process rather than during the state of growth. Sirt2 deacetylated protein(s) bound to the promoter of PDGFRα and simultaneously appeared to facilitate histone3 K27 tri-methylation, both of which are suppressive signatures on gene transcription activation. In bisulfate assay, we identified that Sirt2 significantly induced DNA methylation of PDGFRα promoter compared with the control. Consistently, Sirt2 overexpression down-regulated PDGFRα expression in CG4 cells. The knock-down of PDGFRα or Sirt2 over-expression repressed cell proliferation, but knock-down of Sirt2 promoted cell proliferation. Taken together, Sirt2 translocated into the nuclei while the cells initiated a differentiation process, facilitating CG4 cell differentiation partially through epigenetic modification and suppression of PDGFRα expression. The repression of PDGFRα expression mediated by Sirt2 appeared to facilitate a transition of cellular processes, i.e. from a proliferating progenitor state to a post-mitotic state in CG4 cells.